Efektivitas Kinerja Tenaga Kerja Kontrak Pada Dinas Tenaga Kerja Dan Sertifikasi Kompetensi Kota Denpasar - Yogi Pratiwi, Ni Wayan Sonnia; Winaya, I Ketut; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2019)
ABSTRACT The purpose of this study was to analyze the effectiveness of contract labor performance in the Manpower Office and Denpasar City Competency Certification by using measurement indicators namely quantity, quality, timeliness, adaptability, work performance, and job satisfaction. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicated that the effectiveness of the performance of fully contracted labor can be said to be good but has not been able to be implemented by several contract workers. This can be seen from the six indicators used, where only indicators of quality, adaptability, and work performance have been properly while the indicators of quantity, timeliness, and job satisfaction have not optimaly implemented. Keywords: Effectiveness, Performance, Contract Workers.